Religion, Fertility, and College Type Among College Graduates - Spaeth, Joe L. (Sociological analysis, 1968)
In the first three years after college graduation, graduates of Catholic colleges have more children than other Catholics, who in turn tend to have more children than Protestants, Jews, or agnostics. In the first year of marriage, differences between the two groups of Catholics are not great, but they increase over the next two years. Type of college seems unrelated to the timing of the first child but is related to planning for subsequent ones.